A theoretical room-temperature line list for 15NH3. (February 2015) - Yurchenko, Sergei N.
Abstract: A new room temperature line list for 15 NH3 is presented. This line list comprised of transition frequencies and Einstein coefficients has been generated using the 'spectroscopic' potential energy surface NH3-Y2010 and an ab initio dipole moment surface. The 15 NH3 line list is based on the same computational procedure used for the line list for 14 NH3 BYTe reported recently and should be as accurate. Comparisons with experimental frequencies and intensities are presented. The synthetic spectra show excellent agreement with experimental spectra. Abstract : Highlights: A new room temperature line list for ammonia-15 is presented. The line list contains over 80 million transitions for J up to 18. The synthetic spectra show excellent agreement with experimental spectra. We highlight the gaps and limitations of the existing experimental data.